The Relationship Between Communication in The Family and The Social and Emotional Development of Children Aged 4-5 Years in Batipuh, Tanah Datar Regency - Susanti, Desi; Dasa Putri, Lili (Universitas Negeri Padang, 2023)
The background to this research is the low level of social and emotional development of children. This can be seen from the fact that there are still many children who fight back when reprimanded, are less sensitive to the environment, do not like sharing with other people, children often fight with their friends because they cannot control their emotions. This is suspected to be due to a lack of family communication. This research aims to: 1) See a picture of family communication. 2) See a picture of the social emotional development of children aged 4-5 years. 3) Seeing the relationship between family communication and the social emotional development of children aged 4-5 years in Batipuh.The method used in this study is a quantitative approach with a correlational type. The population in this study were parents who had children aged 4-5 years in Batipuh, Tanah Datar Regency with a total of 47 people and 75% of the samples were 35 people. The sampling used by researchers was cluster random sampling. The data collection technique used was in the form of questionnaires. Data analysis techniques use percentage and product moment formulas. The results of the research show that: 1) Description of family communication in Batipuh, Tanah Datar Regency. 2) The description of the social emotional development of children aged 4-5 years in Batipuh is categorized as less than supportive. 3) There is a relationship between family communication and the social emotional development of children aged 4-5 years in Batipuh. Keywords: Communication, Social emotional development